THE EFFECT OF DIGITAL FINANCIAL TECHNOLOGY AND FINANCIAL LITERACY ON MSME FINANCIAL MANAGEMENT IN MAMBORO BARAT SUB-DISTRICT, NORTH PALU DISTRICT, PALU CITY - Adiba, Ayesha Nurul; Mile, Yuldi; Pakawaru, Muhammad Ilham; Mustamin, Mustamin (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
This study aims to analyze the influence of digital financial technology and financial literacy on the quality of financial management of MSMEs in West Mamboro Village, Palu City. This research uses a quantitative approach with a causal associative method. The study sample consisted of 77 MSMEs, determined using the Slovin formula from a population of 336 MSMEs, using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that digital financial technology has a positive and significant effect on MSME financial management. Financial literacy also has a positive and significant effect and is more dominant. Simultaneously, digital financial technology and financial literacy have a significant effect on MSME financial management, contributing 88.9%. These findings confirm that optimizing MSME financial management is not solely determined by the use of digital financial technology, but also depends heavily on the level of financial literacy of business actors.